Comparison of hydrogeochemical characteristics of thermokarst lake water in the Qinghai–Tibet Plateau under active layer freeze–thaw conditions. Issue 3 (28th January 2022) - Fang, Yahong; Liu, Zejun; Lyu, Qiaofen; Hu, Haiyang; Wang, Wei
Abstract: With the gradual increase of global temperature, thermokarst lakes are widely developed and become major environmental disasters in the Tundra Plateau which have impacted the stability of the project such as the Qinghai–Tibetan highway. In this study, some typical thermokarst lakes in the Qinghai–Tibet Plateau (QTP) were selected as the research object. And four samples were taken from different freezing–thawing processes of the lakes in 2019 to analyze the hydrogeochemical process of the thermokarst lake in the context of climate change. Results show that the main hydrogeochemical types of the lake water in the northern part of the study area were HCO3 ·Cl − Na·Ca·Mg or Cl·HCO3 − Na·Mg, whereas in the central and southern parts were mainly Cl − Na·Mg. The variations of hydrogeochemical concentration in thermokarst lake water are mainly affected by evaporation concentration, rock differentiation, freezing desalination in the active layer, and plant photosynthesis, which are mainly due to temperature changes. Furthermore, the results of the saturation index (SI) show that dolomite and calcite leaching control the hydrogeochemical composition in thermokarst lakes. In addition, the evaporation-to-inflow (E/I) ratios of the lake reach the maximum in the middle and later periods of the active layer thawing. On the contrary, the E/I values of the lakes decrease during the initial thawing or freezing periods of the active layer. HIGHLIGHTS: First, the formation process of hot melt lakes in high-altitude areas is analyzed. Second, the chemical properties of the thermal melting lake in different regions are analyzed, and the reasons that affect the chemical properties are analyzed. Third, through the calculation of the lake (E/I) ratio, the supply relationship between groundwater and lake water and the development of the lake are analyzed.